2011
DOI: 10.1002/sec.377
|View full text |Cite
|
Sign up to set email alerts
|

Secure and efficient dynamic program update in wireless sensor networks

Abstract: Dynamic program update protocols provide a convenient way to reprogram sensor nodes after deployment. However, designing a secure program update protocol for wireless sensor networks is a difficult task because wireless networks are susceptible to attacks and nodes have limited resources. Recently, two secure program update protocols using orthogonality principle have been found to be vulnerable to two impersonation attacks, although these attacks are rather restrictive. This paper reports one new attack that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, we find that Shim's proposed improved protocol is unworkable because the signature verification does not hold true. Among various secure protocols in WSNs [3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][23][24], most of the published reprogramming protocols [3, 6, 12-14, 16, 18, 20-23] are based on the centralized approach, which assumes the existence of a base station, and only the base station has the authority to reprogram sensor nodes. The centralized approach is not reliable in reality because of inefficiency, weak scalability, and vulnerability to potential attacks along the communication path [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we find that Shim's proposed improved protocol is unworkable because the signature verification does not hold true. Among various secure protocols in WSNs [3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][23][24], most of the published reprogramming protocols [3, 6, 12-14, 16, 18, 20-23] are based on the centralized approach, which assumes the existence of a base station, and only the base station has the authority to reprogram sensor nodes. The centralized approach is not reliable in reality because of inefficiency, weak scalability, and vulnerability to potential attacks along the communication path [24].…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al further proposed an improved scheme, but Wang et al [5] pointed out that Zeng et al's proposed protocol [4] still suffers from an impersonation attack. In 2012, He et al [6] showed that an adversary can impersonate a base station to install his/her preferred program on sensor nodes in a WSN, and further, the adversary can control the whole WSN. He et al proposed two simple countermeasures which are formally validated by model checking.…”
Section: Introductionmentioning
confidence: 99%